Společné stanovisko odborných společností k předepisování PCSK9 inhibitorů - Češka, Richard; Táborský, Miloš; Vrablík, Michal (Vnitrni lekarstvi, 2019)
A new class of drugs known as PCSK9 inhibitors (PCSK9i) provide biological treatment for hypercholesterolemia. These drugs are administered using a subcutaneous injection once in two or four weeks. PCSK9i are not a replacement of the existing hypolipidemics, they just expand the therapeutic spectrum for the critically ill and those who cannot use the standard therapy and do not reach satisfactory target values. There are essentially two indications: (1) hypercholesterolemie and mixed dyslipidemia and (2) secondary prevention of cardiovascular diseases (CVD). Statin intolerance is not the only indication for treatment. However as its presence sometimes plays an essential role as to choosing the treatment, it will be also discussed in the paragraph on reimbursement conditions. Reimbursement conditions (very simplified): the treatment will be provided at selected centres. A list of the centres is included in an annexe to this article. You will find it also on www.interna-cz.eu, on www.kardio-cz.cz and www.athero.cz. The indicative concentration of LDL-cholesterol (LDL-C) from which on PCSK9i can be prescribed as covered from the public health insurance, is the following: (1) familial hypercholesterolemia 4.0 mmol/l, (2) for secondary prevention CVD 3.0 mmol/l - Please note: the presented LDL-C level is one reached under maximum (tolerated) high intensity hypo-lipidemic therapy. High intensity hypolipidemic therapy is defined as atorvastatin 40-80 mg or rosuvastatin 20-40 mg + ezetimibe. In the case of demonstrated intolerance of both the mentioned statins the patient has to be treated with a maximum tolerated dose of statins, in combination with another hypolipidemic drug (ezetimibe). Statin intolerance is defined as intolerance of at least two successive statins, which results in their discontinuation. Statin intolerance alone is not the indication for PCSK9i treatment! The payment criteria must always be complied with. A medical officer can of course be asked to approve such treatment in exceptional cases. Key words: alirocumab - PCSK9 inhibitors centers - center therapy - evolocumab - familial hypercholesterolemia - proprotein konvertase subtilisin kexin 9 inhibitors (PCSK9i) - secondary prevention - statins intolerance.
Keywords: hypercholesterolemie; alirocumab - PCSK9 inhibitors centers - center therapy - evolocumab - familial hypercholesterolemia - proprotein konvertase subtilisin kexin 9 inhibitors (PCSK9i) - secondary prevention - statins intolerance; Cholesterol, LDL; Anticholesteremic Agents; směrnice pro lékařskou praxi jako téma; LDL-cholesterol; PCSK9 inhibitory; Antibodies, Monoclonal; lidé; Hypercholesterolemia; Proprotein Convertase 9; Consensus; Humans; anticholesteremika; proproteinkonvertasa subtilisin/kexin typu 9; Practice Guidelines as Topic; konsensus; statiny; monoklonální protilátky; PCSK9 Inhibitors; Hydroxymethylglutaryl-CoA Reductase Inhibitors